Novel Targeting of DNA Methyltransferase Activity Inhibits Ewing Sarcoma Cell Proliferation and Enhances Tumor Cell Sensitivity to DNA Damaging Drugs by Activating the DNA Damage Response - Cristalli, Camilla; Manara, Maria Cristina; Valente, Sergio; Pellegrini, Evelin; Bavelloni, Alberto; De Feo, Alessandra; Blalock, William; Di Bello, Elisabetta; Piñeyro, David; Merkel, Angelika; Esteller, Manel; Tirado, Oscar M.; et al. (Frontiers in Endocrinology, 2022)
DNA methylation is an important component of the epigenetic machinery that regulates the malignancy of Ewing sarcoma (EWS), the second most common primary bone tumor in children and adolescents. Coordination of DNA methylation and DNA replication is critical for maintaining epigenetic programming and the DNMT1 enzyme has been demonstrated to have an important role in both maintaining the epigenome and controlling cell cycle. Here, we showed that the novel nonnucleoside DNMT inhibitor (DNMTi) MC3343 induces a specific depletion of DNMTi and affects EWS tumor proliferation through a mechanism that is independent on DNA methylation. Depletion of DNMT1 causes perturbation of the cell cycle, with an accumulation of cells in the G1 phase, and DNA damage, as revealed by the induction of γH2AX foci. These effects elicited activation of p53-dependent signaling and apoptosis in p53wt cells, while in p53 mutated cells, persistent micronuclei and increased DNA instability was observed. Treatment with MC3343 potentiates the efficacy of DNA damaging agents such as doxorubicin and PARP-inhibitors (PARPi). This effect correlates with increased DNA damage and synergistic tumor cytotoxicity, supporting the use of the DNMTi MC3343 as an adjuvant agent in treating EWS.